Current Researches in Educational Sciences VII - Gündoğar, Ahmet Nedim; Kayhan, Nilay; Topal, İbrahim Halil and Sönmez, Nesrin and Varlık Özsoy, Ece and Gedik, Nuray and Darretxe Urrutxı, Leire and Barrow, Natalie and Gaıntza Jauregı, Zuriñe and Alvarez-Rementeria Alvarez, María and Bakay, Özge and Arıkan, Yüksel Deniz and Eğin, Figen and Akben, Nimet and Şahin, Tuğrul Gökmen (Academician Publishing Book DOI Portal, 2023)
Based in Ankara in Turkey, the independent academic publisher, Akademisyen Publishing House, has been publishing books for almost 30 years. As the directors of Akademisyen Publishing House, we are proud to publish more than 2700 books across disciplines so far, especially in Health Sciences. We also publish books in Social Sciences, Educational Sciences, Physical Sciences, and also books on cultural and artistic topics.